Changes in minor salivary glands during 4-nitroquinoline 1-oxide-induced rat tongue carcinogenesis - Ribeiro, D. A.; Silva, R. N.; Darros, B. R.; Salvadori, Daisy Maria Favero [UNESP]; Marques, MEA (Medimond Publishing Co, 2004)
We investigated the changes of minor salivary glands during 4NQO-induced rat tongue carcinogenesis. Histopathological examinations of serous and mucous tongue salivary glands of 30 male Wistar rats were performed after 4, 12 and 20 weeks of 50 ppm 4NQO chronicle administration in drinking water. Ten rats were used as control. Morphometric results were expressed as volume density (Vv %) of each of the components. Histopathological and morphometric changes in the salivary glands were evident only at 20 weeks following 4NQO administration and they included a significant (P < 0.05) decreased in the mean Vv of the serous acini compared with the control group accompanied by abnormal acini (Vv=14 %). Neither mucous acini nor ducts demonstrated significant changes. In conclusion, minor salivary glands are involved in the progression of 4NQO-induced carcinoma.